3 - Globalisation, Economic Reforms and Democracy in Nigeria - Umezurike, Chuku (Africa Development, 2021)
This article explores how the forces of globalisation have been undermining democratic struggles in Nigeria, particularly through the economic reforms of the Nigerian state. First, the study involves a theoretical demonstration of these relationships. Second, it notes that the relationships between the forces of globalisation and democracy in Nigeria are largely confrontational. This is the case in so far as preindustrial mercantilism, British colonialism, the current transnational effects of foreign direct investment and the multilateral management of contemporary global order have collectively been undermining the democratic struggles of domestic social forces in Nigeria. The study further establishes that there is largely a supportive and reinforcing relationship between the forces of globalisation and economic reform protocols in Nigeria. It finally suggests that although democratic forces in Nigeria have been inducing economic reforms in the country, reform protocols have been reactionary to the forces of democratisation. An analysis of the various economic reforms in Nigeria as a demonstration of this theoretical framework forms the second broad section of the paper. There is also a categorisation of these reforms into two, namely, those that have inadvertently been pursuing economic nationalism of the Nigerian governing elites and those that have directly been structured and oriented towards advancing market liberalisation and state divestiture. Included in the first category are: indigenisation and Nigerianisation; land use; and reforms for poverty alleviation. In the second category are: austerity measures, structural adjustment programme, privatisation and commercialisation which have been embodied in the Structural Adjustment Programmes (SAP) and also in the current practices, the National Economic Empowerment and Development Strategy (NEEDS) and trade and financial liberalisations orchestrated in SAP and post-SAP engagements. The study finally notes that the democratisation of economic reforms in the developing countries is central to genuine global governance.